Signaling Theory - Choudhury, Muntakim (Journal of Accounting, Business and Management (JABM), 2024)
Signaling theory deals with situations under which two parties possess asymmetric information while facing a market interaction. Although this theory originated in information economics, it continues to be used in marketing, entrepreneurship, and management. In this paper, the use of signaling theory in the field of organizational behavior is reviewed and suggestions are provided regarding how this theory can be used in conjunction with attribution theory, sensemaking and sensegiving, impression management, and social identity theory to further research in organization studies.